Validation of a Malay version of the smartphone addiction scale among medical students in Malaysia - Ching, Siew Mooi; Yee, Anne; Ramachandran, Vasudevan; Mohd Sazlly Lim, Sazlyna; Wan Sulaiman, Wan Aliaa; Foo, Loke Loong; Hoo, Fan Kee (Public Library of Science, 2015)
Introduction: This study was initiated to determine the psychometric properties of the Smart Phone Addiction Scale (SAS) by translating and validating this scale into the Malay language (SAS-M), which is the main language spoken in Malaysia. This study can distinguish smart phone and internet addiction among multi-ethnic Malaysian medical students. In addition, the reliability and validity of the SAS was also demonstrated.